Legal Protection Of Separated Creditors In Executing Mortgage Rights On Bankrupt Assembled As Seen In The Face Of Dignified Justice - Heru Siswanto; Yusriyadi; Muh. Afif Mahfud (KRTHA BHAYANGKARA, 2025)
Problem in Article 56 related creditors separatist and preferential is suspension execution goods guarantee for 90 days after debtor stated insolvent , which then can shortened to 2 months . The main obstacles faced creditors separatist is ambiguity about product insolvency — including determination and statement —which causes difficulty in do execution. Theory of justice dignified emphasize importance certainty law and accessibility information as part from solution practical For problem This is for overcome obstacle mentioned , it is suggested existence reformulation in product insolvency and increase transparency as well as accessibility minutes , so that creditors separatist can utilise 2 month period with more effective . Legislators are expected can add editorial regarding the deadline delivery information insolvency as well as ensure easy and transparent access​ For increase justice in the process of execution guarantee.